A visible geography of invisible journeys: Central American migration and the politics of survival. (2018) - Brigden, Noelle K.
Human rights groups have called undocumented Central American migrants the 'invisible victims' of criminal violence in Mexico. However, the geography of the unauthorised migration route through Mexico is highly visible; its location, protocols and violent practices constitute common knowledge in the communities through which it cuts its path. This paper examines the visual cues of the route. Images of places, such as the trailhead, the river at the borders, the migrant shelter and the train yard, provide focal points that orient migrants to the physical terrain. These images also orient activists, providing potent symbols for political contestation in favour of migrants' rights. However, visibility attracts criminal gangs who rob, kidnap and rape migrants, and the gaze of state officials who detain and deport migrants. Thus, this paper traces how geographic icons become beacons to migrants, activists, criminal predators and state actors, and it examines the nature of information and representation under this strategic interaction. It examines how victims and perpetrators become visible to one another.